Effects of extended pharmacological disruption of zebrafish embryonic heart biomechanical environment on cardiac function, morphology, and gene expression. Issue 12 (4th June 2021) - Foo, Yoke Yin; Motakis, Efthymios; Tiang, Zenia; Shen, Shuhao; Lai, Jason Kuan Han; Chan, Wei Xuan; Wiputra, Hadi; Chen, Nanguang; Chen, Ching Kit; Winkler, Christoph; Foo, Roger Sik Yin; Yap, Choon Hwai
Abstract: Background: Biomechanical stimuli are known to be important to cardiac development, but the mechanisms are not fully understood. Here, we pharmacologically disrupted the biomechanical environment of wild‐type zebrafish embryonic hearts for an extended duration and investigated the consequent effects on cardiac function, morphological development, and gene expression. Results: Myocardial contractility was significantly diminished or abolished in zebrafish embryonic hearts treated for 72 hours from 2 dpf with 2, 3‐butanedione monoxime (BDM). Image‐based flow simulations showed that flow wall shear stresses were abolished or significantly reduced with high oscillatory shear indices. At 5 dpf, after removal of BDM, treated embryonic hearts were maldeveloped, having disrupted cardiac looping, smaller ventricles, and poor cardiac function (lower ejected flow, bulboventricular regurgitation, lower contractility, and slower heart rate). RNA sequencing of cardiomyocytes of treated hearts revealed 922 significantly up‐regulated genes and 1, 698 significantly down‐regulated genes. RNA analysis and subsequent qPCR and histology validation suggested that biomechanical disruption led to an up‐regulation of inflammatory and apoptotic genes and down‐regulation of ECM remodeling and ECM–receptor interaction genes. Biomechanics disruption also prevented the formation of ventricular trabeculation along with notch1 and erbb4a down‐regulation. Conclusions: Extended disruption of biomechanical stimuli caused maldevelopment, and potential genes responsible for this are identified. Key Findings: We evaluated the effects of prolonged disruption of heartbeat in the zebrafish embryonic heart (2‐5dpf) on cardiac function, morphology and gene expressions. The disruption led to mal‐development of the heart in terms of abnormal looping angle, smaller ventricle and insufficient heart valves, and it led to poorer cardiac function (lower ejection fraction, regurgitation, slower heart rate, and poorer contractions). Whole transcriptomic analysis showed upregulation of inflammatory and apoptotic genes, downregulation of ECM remodelling and ECM‐receptor interaction. genes, and prevented formation of trabeculation together with not1 and erbb4a downregulation.